The effects of cloud moisture on Restions, Ericas and Proteas in the Cape Floristic region - Gibson, Myfannwyn (Department of Biological Sciences, 2017)
Recent studies on the interception and utilization of occult precipitation (fog, cloud-borne mist and dew) have revealed that the direct wetting of foliage provides a water subsidy to plants of various ecosystem types. In this study, we investigate the presence of foliar uptake, and the effects of misting on the plant water potential of species representing diverse functional types, namely ericoids, proteoids and restioids in Fynbos species occurring within the Cape Fold mist belt. In this study, foliar uptake after 180-min submergence in distilled water was demonstrated by five of the seven species investigated. These species included all the restioids and ericoids investigated in this study. By contrast, the proteoids L. conocarpodendron and L. laureolum were found to show no significant amount of foliar uptake or increased leaf water content (%). There was an increase in the average, normalized leaf water content in individuals subjected to misting treatments in both proteoids, L. laureolum and L. conocarpodendron. Similarly, there was also an overall increase in plant water status, as shown by the increased water potential in individuals that were subjected to the misting treatment. It was found that control individuals showed a decrease in plant water potential (i.e. lost water) during the day, as can be expected when soil water is not replenished. All species showed significant stomatal conductance, during both night and day. Results indicate that misting events have a significant effect on the overall plant water status in all functional types and the presence of foliar uptake in both ericoids and restioids; thus indicating that cloud events may have an important effect on the vulnerability of these species to drought, under the precepts of global climate change.